2018
DOI: 10.1080/00365521.2017.1421705
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis for recurrent primary sclerosing cholangitis after liver transplantation: a Nordic Multicentre Study

Abstract: This study confirms that colectomy before liver transplantation is associated with a decreased risk of rPSC. Inflammatory activity of IBD was not associated with the risk of rPSC. Tacrolimus was an independent risk factor for PSC recurrence and its use as first line immunosuppression in PSC needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 24 publications
8
80
2
4
Order By: Relevance
“…Our institution and others have previously reported a lower incidence of recurrent biliary stricturing disease post‐transplant for patients undergoing colectomy . In the present cohort, we found that this potentially protective effect was confined to patients retaining an end ileostomy (Figure A), whereas the incidence of recurrent biliary strictures was not significantly different between IPAA and no colectomy groups (Figure B).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Our institution and others have previously reported a lower incidence of recurrent biliary stricturing disease post‐transplant for patients undergoing colectomy . In the present cohort, we found that this potentially protective effect was confined to patients retaining an end ileostomy (Figure A), whereas the incidence of recurrent biliary strictures was not significantly different between IPAA and no colectomy groups (Figure B).…”
Section: Resultssupporting
confidence: 61%
“…Herein, we identify that any protective effect conferred following colectomy (with regard to recurrent biliary disease) is skewed towards the patient group retaining an end ileostomy, whereas no benefit is evident for patients with an IPAA. As patients with PSC and IPAA often develop pouchitis and poorer pouch function, it is plausible that persistent or recurrent episodes of intestinal inflammation also contribute to an elevated risk of thrombotic injury, akin to that when the colon is retained . Although speculative, evidence to support this hypothesis includes the fact that our ileostomy group experienced the lowest incidence of hepatic artery thrombosis; in addition to findings that show persistent subclinical intestinal inflammation in PSC associated colitis, associations between pouchitis and thrombocytosis, and heightened platelet activation during active IBD…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recurrent PSC after LT was reported in Pittsburgh in 1988 . Recurrence occurs in 17–27% of cases with a duration of 8 months to 6 years . The diagnosis of PSC recurrence in a graft liver is often difficult.…”
Section: Disease Recurrence and Management Post‐ltmentioning
confidence: 99%
“…74 Recurrence occurs in 17-27% of cases with a duration of 8 months to 6 years. [75][76][77][78][79][80] The diagnosis of PSC recurrence in a graft liver is often difficult. An increase in hepatobiliary enzymes and narrowing of the bile duct on a magnetic resonance cholangiography image, stenosis, and dilation are the basis for the clinical diagnosis, but an occluded hepatic artery also shows the same demographics.…”
Section: Primary Biliary Cholangitis and Primary Sclerosing Cholangitismentioning
confidence: 99%